2020
DOI: 10.3389/fphar.2019.01601
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Chemotherapies and Stem Cell Transplantation for Systemic AL Amyloidosis: A Network Meta-Analysis

Abstract: Background/Aims: The present Bayesian network meta-analysis (NMA) was to compare the efficacy of different chemotherapies and autologous stem cell transplantation (ASCT) in immunoglobulin light-chain (AL) amyloidosis. Methods:We systematically searched PubMed, Embase, Web of Science, and the Cochrane Central Register of Controlled Trials (CENTRAL) for studies compared the rates of hematological response (HR), complete response (CR), renal response, and cardiac response in AL amyloidosis patients.Results: There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…A regimen including bortezomib, a proteasome inhibitor, with or without corticosteroids, is a highly efficacious alternative to HCT. 15,16 Options for disease that has relapsed or is refractory to initial therapy include daratumumab, an anti-CD38 monoclonal antibody, proteasome inhibitor regimens, or immunomodulatory regimens. 17 The choice of therapy is decided on according to patient-specific disease and social factors, some of which may be linked to a more favorable response to certain therapies.…”
Section: Discussionmentioning
confidence: 99%
“…A regimen including bortezomib, a proteasome inhibitor, with or without corticosteroids, is a highly efficacious alternative to HCT. 15,16 Options for disease that has relapsed or is refractory to initial therapy include daratumumab, an anti-CD38 monoclonal antibody, proteasome inhibitor regimens, or immunomodulatory regimens. 17 The choice of therapy is decided on according to patient-specific disease and social factors, some of which may be linked to a more favorable response to certain therapies.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis involving three randomized controlled trials (RCTs) and thirteen observational controlled trials (OCTs) comparing seven treatment regimens: High dose melphalan followed by autologous stem cell transplant (HDM/HSCT), Melphalan + dexamethasone (MDex), Bortezomib + melphalan + dexamethasone (BMDex), Bortezomib + dexamethasone (BDex), Thalidomide + cyclophosphamide + dexamethasone (CTD), Bortezomib + Cyclophosphamide + dexamethasone (CyBorD), cyclophosphamide + lenalidomide + dexamethasone (CLD) showed BMDex ranking high in terms of hematologic response and complete response (CR), CTD ranking high in terms of renal response and BDex was best treatment for cardiac response [ 31 ].…”
Section: Indications For Systemic Therapymentioning
confidence: 99%
“…18,19 A retrospective study from our own center also showed that CTD was an effective and safe option for treating AL patients with renal involvement. 20 A recently published network meta-analysis 21 concluded that CTD could induce the highest rate of renal response and BDex was associated with highest cardiac response rate. There has been a retrospective comparison of cyclophosphamide, bortezomib, and dexamethasone versus CTD, 16 but no direct comparison of BDex and CTD has been reported.…”
Section: Introductionmentioning
confidence: 99%